Aging with Dignity: Exploring the Imperative of Universal Social Pension - Agnihotri, Aastha (MultiTech Publisher, 2023)
This research addresses the multifaceted challenges faced by older individuals in terms of financial security and the implications for their ability to age with dignity. By examining the impact of aging on economic well-being, the study delves into the theoretical foundations and practical implementations of universal social pension programs globally. It explores the dynamic interplay between financial constraints and dignified aging, considering aspects such as healthcare access, social participation, and overall well-being. A critical component of the research involves assessing the impact of aging on financial security, evaluating the relationship between financial security and dignified aging, identifying opportunities for improving universal social pension programs and providing recommendations for policy and practice. This research contributes valuable insights to the academic discourse on aging and social welfare, fostering a deeper understanding of the complexities inherent in ensuring dignified aging. The findings are anticipated to inform policy decisions, shape interventions, and contribute to the ongoing global dialogue on creating inclusive environments that prioritize the well-being and dignity of the aging population.